Using hot potato game in teaching speaking to elementary school students in Regaji Village Karo Regency (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2020)
Speaking is the skill prioritized in teaching English to elementary school students. However, English teachers frequently encounter problems in teaching speaking or in motivating them to speak English. Therefore, teachers have to find an appropriate technique or media that can solve such a problem. One of the techniques that can be used is using games, such as the hot potato game. This paper aims at describing the use and the advantages of hot potato game in teaching speaking to elementary school students. This study used a descriptive method taking the elementary school teacher and students in Regaji Village of Karo Regency, North Sumatra, as the participants. The data were the process of teaching and learning English using the hot potato game as the technique. The data were collected using observations and interviews and were analyzed qualitatively. The results of the analysis show that using the hot potato game in teaching speaking to elementary school students provides several advantages: (i) creating a fun learning atmosphere; (ii) improving the students’ motivation in learning English; (ii) generating students’ competitiveness in learning English; (iii) helping students to improve their vocabulary stock; and (iv) positively changing the students’ view of learning English. It is concluded that using the hot potato game is a good technique in teaching speaking English to elementary school students.